Next-Generation Sequencing and Genome Editing in Plant Virology - Hadidi, Ahmed; Flores, Ricardo; Candresse, Thierry; Barba, Marina (Frontiers in Microbiology, 2016)
Next-generation sequencing (NGS) has been applied to plant virology since 2009. NGS provides highly efficient, rapid, low cost DNA or RNA high-throughput sequencing of the genomes of plant viruses and viroids and of the specific small RNAs generated during the infection process. These small RNAs, which cover frequently the whole genome of the infectious agent, are 21-24 nt long and are known as vsRNAs for viruses and vd-sRNAs for viroids. NGS has been used in a number of studies in plant virology including, but not limited to, discovery of novel viruses and viroids as well as detection and identification of those pathogens already known, analysis of genome diversity and evolution, and study of pathogen epidemiology. The genome engineering editing method, clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 system has been successfully used recently to engineer resistance to DNA geminiviruses (family, Geminiviridae) by targeting different viral genome sequences in infected Nicotiana benthamiana or Arabidopsis plants. The DNA viruses targeted include tomato yellow leaf curl virus and merremia mosaic virus (begomovirus); beet curly top virus and beet severe curly top virus (curtovirus); and bean yellow dwarf virus (mastrevirus). The technique has also been used against the RNA viruses zucchini yellow mosaic virus, papaya ringspot virus and turnip mosaic virus (potyvirus) and cucumber vein yellowing virus (ipomovirus, family, Potyviridae) by targeting the translation initiation genes eIF4E in cucumber or Arabidopsis plants. From these recent advances of major importance, it is expected that NGS and CRISPR-Cas technologies will play a significant role in the very near future in advancing the field of plant virology and connecting it with other related fields of biology. Keywords: Next-generation sequencing, NGS, plant virology, plant viruses, viroids, resistance to plant viruses by CRISPR-Cas9